Handbook of Trends in Engineering Technology and Research(Volume 1) - Chitaranjan Dalai ,; Chandra Kumar Dixit ,; Suryabhan Pratap Singh, (AG Volumes, 2022)
The ecosystem is important for sustaining of life on Earth. When we degrade the environment with the human-made garbage, it leads to significant environmental challenges for the world. Nevertheless, many of us aren’t paying notice to the issues generated in the environment, that is going to be a big concern for the generations to come. Due to high levels of pollution, there’s an alarming growth in environmental difficulties preparing the way for the loss of the natural resources. This paper takes a deep look at the environmental concerns and numerous developing technologies in the area of the environmental science in order to remedy the issue.